1997
DOI: 10.1016/s0014-5793(97)01426-9
|View full text |Cite
|
Sign up to set email alerts
|

The IL1 receptor accessory protein is responsible for the recruitment of the interleukin‐1 receptor associated kinase to the IL1/IL1 receptor I complex

Abstract: Following interleukin-1 (ILl) stimulation, an ILl receptor associated kinase (IRAK) is rapidly recruited to the receptor complex. However, it is not understood if IRAK is able to interact directly with the intracellular portion of the IL1-RI or if its recruitment is mediated by a different molecule. Using the yeast two-hybrid system, we have analysed possible proteinprotein interactions between IRAK, IL1-RI and ILl-RAcP. We found that IRAK is able to interact with the equivalent cytoplasmic region of the ILl-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 16 publications
(14 reference statements)
1
32
0
Order By: Relevance
“…The amplified sequence found was identical with that described previously (26). pFLAG-IL-1RAcP, which produces flag-tagged IL-1R accessory protein (27), was a gift from Dr. F. Volpe, Glaxo-Wellcome (Stevenage, U.K.). pCDM8-CD14 (28) was a gift from Prof. B.…”
Section: Cdna Preparationmentioning
confidence: 69%
See 1 more Smart Citation
“…The amplified sequence found was identical with that described previously (26). pFLAG-IL-1RAcP, which produces flag-tagged IL-1R accessory protein (27), was a gift from Dr. F. Volpe, Glaxo-Wellcome (Stevenage, U.K.). pCDM8-CD14 (28) was a gift from Prof. B.…”
Section: Cdna Preparationmentioning
confidence: 69%
“…To investigate the mechanism of the observed TLR1-TLR2 cooperation, TLR2 was cotransfected with vectors directing expression of TLR1, TLR1⌬cyt, or the accessory chain of the IL-1R (IL1RAcP) (27), which contains a TIR signaling domain related to those of TLRs (3). We reasoned that if the increase in signaling was a nonspecific effect due to increased expression of TIR domains, then IL-1RAcP might substitute for TLR1.…”
Section: Full-length Tlr1 Is Required For Tlr2-dependent Responses Tomentioning
confidence: 99%
“…Although previous studies have shown that the IL-1 receptors localize to focal contact sites in human fibroblasts and keratinocytes (41)(42)(43) and that IRAK and IL-1R I associate in IL-1-stimulated cells (45), a physical association between IRAK, IL-1R 1 , and focal adhesions has not been established. We first determined by immunoblot analysis that IL-1R 1 could be detected in beadassociated complexes at 10 and 20 min following the addition of collagen-coated microbeads to fibroblasts (Fig.…”
Section: Irak Recruitment Into Nascent Facs Requires Il-1-facsmentioning
confidence: 95%
“…IL1RAP is an essential component of the IL-1 coreceptor complex required for IL-1β-induced signaling (8)(9)(10). Coexpression of IL1RAP and IL-1RI can mimic IL-1β stimulation for activation of NF-κB (Fig.…”
Section: Identification Of March8 As a Negative Regulator Of Il-1β-inmentioning
confidence: 99%
“…IL-1RI is the ligand-recognition receptor that binds IL-1β directly (7). Although IL1RAP does not bind IL-1β directly, its recruitment to IL-1RI following IL-1β stimulation is essential for the formation of an activated membrane receptor complex (8)(9)(10)). The activated complex can then recruit intracellular adaptor proteins and kinases, including MyD88, IRAK4, and IRAK1 (11)(12)(13)(14).…”
mentioning
confidence: 99%